Lead exposure from general aviation emissions in the UK: A review and call for action - Ashley Mills; Stephen Peckham (Wiley, 2022)
Abstract Leaded fuel emissions exposed a global population of children to lead and its profound health consequences. Recognition of its harms precipitated a global phase out and replacement with unleaded substitutes for road vehicles. Despite this widespread recognition and action, aviation fuel for piston engine aircraft still contains lead. Leaded aviation fuel (AVGAS100LL) contains 0.56 g of tetraethyl lead (TEL) per litre and this lead must be jettisoned from the engine during operation to prevent fouling. This action distributes lead and lead compounds into the air and soil around general aviation airports. This has been shown to increase the blood lead levels (BLLs) of children living nearby to clinically significant levels. Whilst this problem is recognised by the EPA in the United States, it has received little attention in the United Kingdom. We provide a review of the situation in the United Kingdom with regard to the current policy and regulation framework. We analysed the UK's general aviation airport fleet, general avation airport data and GB residential address data. We estimate the unleaded‐readiness of the UK aviation fleet and the current usage of fuels at UK general aviation airports. We provide a first‐order estimate of the number of residential addresses exposed to lead near general aviation airports. We find that the majority of aviation fuel sold in the United Kingdom is leaded and that there are 370,632 residences within 4 km of a general aviation airport at risk from exposure to lead emissions. Finally, we present a path forward for regulation change and public health monitoring.